Estímulos fiscales para empresas que utilizan energías limpias - Contreras Villaseñor, Lluvia (Universidad Michoacana de San Nicolás de Hidalgo, 2017)
The state to be able to meet public needs and meet collective needs must find resources through different means. One of them is the contributions whose purpose may be extra-fiscal, that is, its main purpose is not collection, and serve as policy instruments Economic and social. Tax incentives are economic benefits that the state grants to taxpayers to encourage or discourage an activity and thus achieve a social purpose. Due to the negative consequences of the excessive use of pollutants, and industrialization, such as environmental deterioration, global warming and disease increase, coupled with OECD recommendations, Mexico as part of its environmental policies establishes fiscal incentives for companies which use clean energy. The purpose of these incentives is to motivate companies to change their mechanisms from non-renewable to renewable energies and thereby avoid the depletion of fossil reserves of petroleum coal; As well as reduce greenhouse gas emissions and use energy that is more environmentally friendly. These incentives consist in increasing the limits of deductions to companies that invest in equipment that contribute to the care of the environment, as well as the granting of tax credits. For companies, the use of clean energy implies a cost; when applying the fiscal stimulus, they benefit from a reduction in the tax burden; In addition, the use of these energies gives those significant savings in operating expenses that make their investment profitable It is vital that companies are aware of the fiscal incentives to which they can access, what they consist of, the requirements and procedure to obtain them and the benefit that will have to be applied; as well as the correct treatment that should be given and the obligations established by the laws for those who benefit from fiscal stimulus.

El Estado para poder sufragar el gasto público y satisfacer las necesidades colectivas debe de allegarse de recursos a través de distintos medios, uno de ellos son las contribuciones cuya finalidad puede ser extrafiscal, es decir que su principal propósito no sea la recaudación, y sirven como instrumentos de políticas económicas, financieras y sociales. Los estímulos fiscales son beneficios económicos que otorga el Estado a los contribuyentes para alentar o desalentar una actividad y así lograr un fin social. Debido a las consecuencias negativas del uso desmedido de contaminantes y la industrialización como lo son: el deterioro ambiental, el calentamiento global y el incremento de enfermedades, aunado a recomendaciones de la OCDE, México como parte de sus políticas ambientales establece estímulos fiscales para empresas que utilizan energías limpias. La finalidad de estos estímulos es motivar a las empresas a cambiar sus mecanismos de energías no renovables a renovables y con ello evitar el agotamiento de las reservas fósiles, de carbón y de petróleo; así como disminuir las emisiones de gases de efecto invernadero y utilizar energías que son más amigables con el medio ambiente. Para las empresas la utilización de energías limpias implica un costo, al aplicar los estímulos fiscales se ven beneficiadas con una reducción en la carga fiscal; además la utilización de estas energías les proporciona importantes ahorros en gastos operativos que hacen que su inversión sea rentable. Es de vital importancia que las empresas tengan conocimiento de los estímulos fiscales a los que pueden acceder, en qué consisten, los requisitos y procedimiento para obtenerlos y el beneficio que se tendrá de aplicarlos; así como el correcto tratamiento que se les debe dar y las obligaciones que establecen las leyes para quienes se beneficien de estímulos fiscales.
Facultad de Contaduría y Ciencias Administrativas. Maestría en Fiscal
Keywords: info:eu-repo/classification/cti/5; FCCA-M-2017-1589; Impuestos; Deducción; Contaminación; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/6135